2017
DOI: 10.1371/journal.pmed.1002340
|View full text |Cite
|
Sign up to set email alerts
|

Risk of surgical site infection, acute kidney injury, and Clostridium difficile infection following antibiotic prophylaxis with vancomycin plus a beta-lactam versus either drug alone: A national propensity-score-adjusted retrospective cohort study

Abstract: BackgroundThe optimal regimen for perioperative antimicrobial prophylaxis is controversial. Use of combination prophylaxis with a beta-lactam plus vancomycin is increasing; however, the relative risks and benefits associated with this strategy are unknown. Thus, we sought to compare postoperative outcomes following administration of 2 antimicrobials versus a single agent for the prevention of surgical site infections (SSIs). Potential harms associated with combination regimens, including acute kidney injury (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 31 publications
0
64
0
1
Order By: Relevance
“…At present, in the USA and Canada, around 40 per cent of patients are given oral antibiotics in combination with MBP6. The combination of oral neomycin and erythromycin has been recommended for use as preoperative antibiotic prophylaxis for colorectal surgery in an advisory statement from the Medicare National Surgical Infection Prevention Project35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in the USA and Canada, around 40 per cent of patients are given oral antibiotics in combination with MBP6. The combination of oral neomycin and erythromycin has been recommended for use as preoperative antibiotic prophylaxis for colorectal surgery in an advisory statement from the Medicare National Surgical Infection Prevention Project35.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for avoidance of MBP in Europe are multifactorial, but the trend towards enhanced recovery after surgery (ERAS) protocols that exclude routine MBP is probably a significant contributor5. Concerns regarding hospital‐acquired infections including Clostridium difficile are relevant only when patients are exposed to extended bowel‐cleansing protocols6. The aim of this review was to assess only trials that included 1 day of preoperative antibiotics, and all trials assessing longer periods of preoperative antibiotic exposure were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have had this major surgery are at risk for certain severe postoperative infections. It has been reported that the incidence of sternal surgical site infections after open heart surgery ranges from 1.3 to 8.6% (1,2), and the incidence of deep sternal infections, such as mediastinitis, is 4.6% (2). Furthermore, the 1-year mortality rate increases for patients with deep sternal infections to reach ϳ22% (3).…”
mentioning
confidence: 99%
“…reported in a national VA cohort that patients who received vancomycin as a preoperative prophylaxis had an increased risk of postoperative acute kidney injury. Moreover, the rate of vancomycin use as preoperative antibiotic in patients who underwent cardiac (bypass procedures, valve repairs, and repair of structural heart disease) procedures; orthopedic joint replacement; or vascular, colorectal, or hysterectomy procedures ranged up to 25% . Courtney et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Branch-Elliman et al reported in a national VA cohort that patients who received vancomycin as a preoperative prophylaxis had an increased risk of postoperative acute kidney injury. Moreover, the rate of vancomycin use as preoperative antibiotic in patients who underwent cardiac (bypass procedures, valve repairs, and repair of structural heart disease) procedures; orthopedic joint replacement; or vascular, colorectal, or hysterectomy procedures ranged up to 25% 36. Courtney et al also showed that patients who received combined vancomycin and cefazolin as prophylaxis for primary joint arthroplasty had a significantly higher risk of acute kidney injury as compared to patients who received cefazolin alone 22.…”
mentioning
confidence: 99%